1960
DOI: 10.1084/jem.111.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of the Shwartzman Phenomenon

Abstract: Intradermal injections of bacterial endotoxins in normal rabbits ordinarily yield delayed inflammatory reactions which are not manifest in the gross for several hours and reach maximal development only after a day or more. While the mechanism underlying these characteristic cutaneous reactions is not understood, it has been pointed out that the reactions resemble, in many respects, those of delayed hypersensitivity (1). The present study was prompted by recent chance observations which suggested that the derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1963
1963
1975
1975

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…LEE [26] has shown that in the presence of reticuloendothelial blockage injection of antigen into specifically immunized rabbits or the infusion of soluble antigen-antibody complexes in normal rabbits will lead to the development of renal cortical necrosis. The fact that cross-reactive antibodies to endotoxins have been demonstrated in rabbit sera [39], and that other similarities have been described between the effects produced by endotoxins and by antigen-antibody complexes [30,41.42] offers the possibility that endotoxin may exert its effect on intravascular clotting by virtue of its antigenicity. Thus the endotoxin-induced Shwartzman phenomenon may be but one example of a broad biologic phenomeon having its origin in antigen-antibody reactions and its expression in intravascular clotting.…”
Section: Discussionmentioning
confidence: 99%
“…LEE [26] has shown that in the presence of reticuloendothelial blockage injection of antigen into specifically immunized rabbits or the infusion of soluble antigen-antibody complexes in normal rabbits will lead to the development of renal cortical necrosis. The fact that cross-reactive antibodies to endotoxins have been demonstrated in rabbit sera [39], and that other similarities have been described between the effects produced by endotoxins and by antigen-antibody complexes [30,41.42] offers the possibility that endotoxin may exert its effect on intravascular clotting by virtue of its antigenicity. Thus the endotoxin-induced Shwartzman phenomenon may be but one example of a broad biologic phenomeon having its origin in antigen-antibody reactions and its expression in intravascular clotting.…”
Section: Discussionmentioning
confidence: 99%